2018
DOI: 10.1021/jacs.8b08135
|View full text |Cite
|
Sign up to set email alerts
|

Direct and Regioselective C–H Oxidative Difluoromethylation of Heteroarenes

Abstract: The difluoromethyl group (CFH) is of great interest in the area of medicinal chemistry. However, the investigation of molecular scaffolds containing this group has been hampered by the limitation of synthetic methods for the introduction of CFH into heteroarenes. Herein we disclose a new strategy for the direct introduction of a difluoromethyl group into heteroarenes via the copper-mediated C-H oxidative difluoromethylation of heteroarenes with TMSCFH. This mild and regioselective method enables the convenient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
42
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(42 citation statements)
references
References 82 publications
0
42
0
Order By: Relevance
“…An examination of the substituent effects in aryl alkenes showed that neither electron-withdrawing nor -donating groups had an obvious impact on the yields.A variety of functional groups were tolerated, such as ether, ester,k etone,c hloride,b romide,i odide,b oronic acid ester, and amide groups.The compatibility of this reaction with the reactive functional groups,i ncluding bromide (4-14, 4-15, 4-24), iodide (4-16), and boronic acid ester (4-12), allowed further CÀCc oupling transformations.T he HCF 2 /CN-containing estrone derivatives were synthesized by this cyanodifluoromethylation conversion, further demonstrating the synthetic utility of this method (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). An examination of the substituent effects in aryl alkenes showed that neither electron-withdrawing nor -donating groups had an obvious impact on the yields.A variety of functional groups were tolerated, such as ether, ester,k etone,c hloride,b romide,i odide,b oronic acid ester, and amide groups.The compatibility of this reaction with the reactive functional groups,i ncluding bromide (4-14, 4-15, 4-24), iodide (4-16), and boronic acid ester (4-12), allowed further CÀCc oupling transformations.T he HCF 2 /CN-containing estrone derivatives were synthesized by this cyanodifluoromethylation conversion, further demonstrating the synthetic utility of this method (4)(5)(6)(7)(8)…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…An examination of the substituent effects in aryl alkenes showed that neither electron-withdrawing nor -donating groups had an obvious impact on the yields.A variety of functional groups were tolerated, such as ether, ester,k etone,c hloride,b romide,i odide,b oronic acid ester, and amide groups.The compatibility of this reaction with the reactive functional groups,i ncluding bromide (4-14, 4-15, 4-24), iodide (4-16), and boronic acid ester (4-12), allowed further CÀCc oupling transformations.T he HCF 2 /CN-containing estrone derivatives were synthesized by this cyanodifluoromethylation conversion, further demonstrating the synthetic utility of this method (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). An examination of the substituent effects in aryl alkenes showed that neither electron-withdrawing nor -donating groups had an obvious impact on the yields.A variety of functional groups were tolerated, such as ether, ester,k etone,c hloride,b romide,i odide,b oronic acid ester, and amide groups.The compatibility of this reaction with the reactive functional groups,i ncluding bromide (4-14, 4-15, 4-24), iodide (4-16), and boronic acid ester (4-12), allowed further CÀCc oupling transformations.T he HCF 2 /CN-containing estrone derivatives were synthesized by this cyanodifluoromethylation conversion, further demonstrating the synthetic utility of this method (4)(5)(6)(7)(8)…”
mentioning
confidence: 92%
“…[2] Thei ncorporation of aH CF 2 group into organic molecules has garnered significant attention. [2,3] Because difluoromethylation is the most straightforward strategy for incorporation of HCF 2 into organic molecules,m any difluoromethylation reagents have been developed, [4] such as TMSCF 2 H [5] and XCF 2 H( X= F, Cl, or Br). [6] Simultaneous incorporation of as econd functional group into molecules would allow further transformation;t he second functional group could also have excellent potential for the design of pharmaceuticals and agrochemicals.T herefore,m uch effort has been devoted to development of efficient methods for difluoromethylative difunctionalization of alkenes,i ncluding hydrodifluoromethylation, [7] carbodifluoromethylation, [8] oxydifluoromethylation, [9] and halodifluoromethylation.…”
mentioning
confidence: 99%
“…On contrary, compounds 4, 8B, 12, 15, and 16 showed broad signals in the regions δ11.73-9.53 ppm due to NH protons. The protons of OH groups which attached to phosphorus atoms in the products 7B, 8B, 11, and 12 appeared as broad signals in the regions δ5.66-4.30 ppm [19]. The chemical shifts of the aromatic protons for all the products appeared in region δ8.18-6.91 ppm.…”
Section: Resultsmentioning
confidence: 95%
“…Ag ram-scale conversion was performed and a6 9% isolated yield of 4-1 was obtained, revealing the potential application of this reaction. An examination of the substituent effects in aryl alkenes showed that neither electron-withdrawing nor -donating groups had an obvious impact on the yields.A variety of functional groups were tolerated, such as ether, ester,k etone,c hloride,b romide,i odide,b oronic acid ester, and amide groups.The compatibility of this reaction with the reactive functional groups,i ncluding bromide (4-14, 4-15, 4-24), iodide (4-16), and boronic acid ester (4-12), allowed further CÀCc oupling transformations.T he HCF 2 /CN-containing estrone derivatives were synthesized by this cyanodifluoromethylation conversion, further demonstrating the synthetic utility of this method (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). Internal alkenes showed low reactivity,which resulted in alower yield (4-25).…”
mentioning
confidence: 92%